1998
DOI: 10.2337/diacare.21.11.1876
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of the quality of life of patients with diabetes under intensified insulin therapy.

Abstract: The hypothesis that the various factors involved in the multidimensional construct QOL receive different weightings was confirmed, making a simple summary score for the general QOL appear unjustifiable. In addition, all aspects that are commonly understood as parameters of QOL are influenced by external factors, such as coping behavior, based on individual personality characteristics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
11

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 0 publications
1
33
0
11
Order By: Relevance
“…Overall HRQoL in diabetes is affected by various domains of functioning and well-being, implying the need for a multidimensional measurement approach. 42 However, it is usually the combined effect of macrovascular and microvascular complications, comorbid conditions, and background demographic, clinical and treatment satisfaction variables which degrade HRQoL and not diabetes per se. 43 The results of the known-groups comparisons performed here conform to the literature 1,[12][13][14][15]17,[27][28][38][39][40][41] in terms of the score differences and the direction of these differences.…”
Section: Discussionmentioning
confidence: 99%
“…Overall HRQoL in diabetes is affected by various domains of functioning and well-being, implying the need for a multidimensional measurement approach. 42 However, it is usually the combined effect of macrovascular and microvascular complications, comorbid conditions, and background demographic, clinical and treatment satisfaction variables which degrade HRQoL and not diabetes per se. 43 The results of the known-groups comparisons performed here conform to the literature 1,[12][13][14][15]17,[27][28][38][39][40][41] in terms of the score differences and the direction of these differences.…”
Section: Discussionmentioning
confidence: 99%
“…We find that depressed subjects generally have a poorer quality of life, independent of the physical illnesses from which they might suffer (9 -12). This also applies to patients with diabetes whose personality dispositions appear to be more significant for the quality of life than, for instance, the presence of secondary illnesses (8,13,14). The patient's psychological disposition is, in turn, closely connected to cognitive and emotional aspects of his/her illness-coping strategies, which indirectly affect their healthseeking behavior (15).…”
Section: Quality Of Lifementioning
confidence: 99%
“…Earlier studies have suggested that obesity (BMI >30) and depression may also be significant predictors of health-related quality of life and patient utility in type 2 diabetes [7,8,11,12]. Initially, we chose not to include these among our predictor variables: obesity is not necessarily a morbid condition per se, and in the context of type 2 diabetes may be both a cause and a consequence of developing metabolic dysfunction; depression is also not recognised as a primary complication of diabetes, and may be more properly seen as a secondary outcome consequent on other complications.…”
Section: General Principles and Assumptionsmentioning
confidence: 99%